2021
DOI: 10.1186/s43055-021-00575-1
|View full text |Cite
|
Sign up to set email alerts
|

Value of sonographic pseudogestational sac sign in the diagnosis of Meckel diverticulum in children presenting with bleeding per rectum: a 15-year prospective study

Abstract: Background Meckel diverticulum is the most common congenital abnormality of the gastrointestinal tract. Gastrointestinal bleeding is the most common complication of Meckel diverticulum in the paediatric population; the bleeding mostly occurs in the first 2 years of life. Because the diverticulum is seldom seen in clinical practice, misdiagnosis and delayed diagnosis are not uncommon. CT and nuclear studies are the most used diagnostic tools in clinical practice. However, radiation and sensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
0
0
Order By: Relevance
“…Recent studies have showed high sensitivity and specificity in diagnosis of bleeding MD in pediatric patients. 11 , 12 Scintigraphy, using Technetium‐99m (Tc‐99m) pertechnetate, is preferred in pediatric patients with lower gastrointestinal bleeding due to its high sensitivity and specificity of 0.80 (95% CI 0.73–0.86) and 0.95 (95% CI 0.86–0.98) for detecting ectopic gastric tissue within MD in children. 13 In adults, however, its diagnostic accuracy is lower (20%–60%).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have showed high sensitivity and specificity in diagnosis of bleeding MD in pediatric patients. 11 , 12 Scintigraphy, using Technetium‐99m (Tc‐99m) pertechnetate, is preferred in pediatric patients with lower gastrointestinal bleeding due to its high sensitivity and specificity of 0.80 (95% CI 0.73–0.86) and 0.95 (95% CI 0.86–0.98) for detecting ectopic gastric tissue within MD in children. 13 In adults, however, its diagnostic accuracy is lower (20%–60%).…”
Section: Discussionmentioning
confidence: 99%